Numerical Comparisons for Various Estimators of Slope Parameters (MATEMATIKA, 2004)
Berbagai penganggar konsistent telah dicadangkan untuk parameter kecerunan bagi hubungan fungsian linear tanpa replika. Artikel ini memberikan perbandingan berangka bagi penganggar-penganggar tersebut. Adalah diharapkan kita dapat mencadangkan pemilihan yang sesuai baginya. Katakunci: Penganggar konsistent; parameter kecerunan; hubungan fungsian linear tanpa replika. A variety of consistent estimators of the slope parameter for unreplicated linear functional relationship model have been proposed over the years. This paper gives some numerical comparisons among them. As a result we are able to make specific recommendations regarding a choice among them. Keywords: Consistent estimator; slope parameter; unreplicated linear functional relationship model.